EU cohesion policy and spatial governance : territorial, social and economic challenges - Rauhut, Daniel; Sielker, Franziska, 1986-; Humer, Alois (Edward Elgar Publishing, 2021)
"Discussing the ongoing and future challenges of EU Cohesion Policy, this book critically addresses the economic, social and territorial challenges at the heart of the EU's policy. It identifies the multifaceted and dynamic nature of the policy as well as the cohesions goal interlinkage with other policies and considers unresolved questions of strategic importance in territorial governance, urban and regional inequalities, and social aspects and wellbeing. Interdisciplinary perspectives offer well-founded historical views, conceptual thoughts, policy insights and empirical analyses of EU Cohesion Policy, exploring under-represented territorial and spatial perspectives. Fostering a long term, visionary debate, the book looks into the controversial aspects of the policy. It concludes with a rich synthesis of the debate, emphasising three key concerns: disintegration as an alternative to the eroding idea of greater European integration; the discontent of cities and regions due to widening inequalities; the discretion of member states which prevents the EU from engaging more deeply with social issues. With commentaries on each of the key areas provided by top scholars, this book will be an invigorating read for EU policy makers keen to gain a more critical understanding of key issues around territorial, social and economic cohesion. It will also be an insightful read for economic geography, spatial planning, political science, international relations, European studies and social science scholars in general"- Resumé vydavatel
Keywords: Evropské hospodářské společenství; Evropská unie; regionální rozdíly -- země Evropské unie; hospodářská politika -- země Evropské unie; veřejná politika -- země Evropské unie; regional disparities -- European Union countries; economic policy -- European Union countries; public policy -- European Union countries; elektronické knihy; kolektivní monografie; electronic books; collective monographs